I wonder why the sea is salty : and other questions about the oceans - Ganeri, Anita (London : Kingfisher, 1995)
A further title from the question and answer series I WONDER WHY, with colour artwork and cartoons, an examination of the physical geography of seashores, islands and oceans, the animals that live in the oceans and human exploration of deep water, with unusual facts and analogies.
Children
Keywords: Ocean$1 (BJuvenile literature; Ocean$1 (BPictorial works; Children's questions and answerss